The influence of parental attachment on the social-emotional development of children with autism - Megantara, Adinda Thalia; Chailan Salsabila, Hanum; Fahira Sari, Alifia; Nazhwa Pragista, Farah; Dian Pertiwi, Adharina (Al-Athfaal: Jurnal Ilmiah Pendidikan Anak Usia Dini, 2025)
Background : Parental attachment is a fundamental aspect of a child’s early development and serves as a foundation for their future well-being. For children with autism, secure attachment becomes even more essential, as it directly supports their ability to engage socially and regulate emotions. Despite its importance, few studies have qualitatively explored how real-life parenting practices influence the social-emotional development of autistic children, particularly in contexts where parents serve as the primary caregivers and use alternative communication methods. Aim : This study aims to examine the influence of parental attachment on the social-emotional development of children with autism. It also seeks to offer a deeper insight by comparing direct and indirect parenting practices and exploring actual caregiving behaviors that have rarely been addressed in contextual qualitative research. Method : A qualitative case study approach was used, with purposive sampling to select participants aligned with the study objectives. The subject of this research was a parent of an eight-year-old child diagnosed with autism. Data were collected through observation and in-depth interviews, focusing on the daily parenting interactions and communication strategies employed. Result : The findings indicate that the child exhibits a relatively strong attachment to the parent, which is attributed to being directly raised by them. The parent frequently uses body language and gestures to communicate, compensating for the child’s limited verbal abilities. The child does not display fear in unfamiliar settings and is able to express themselves confidently in new environments. This behavior suggests that the secure attachment has fostered a sense of emotional safety and social adaptability. Conclusion : Parental attachment significantly influences the social-emotional development of children with autism. Direct caregiving, emotional attunement, and the use of adaptive communication strategies contribute to the child’s confidence and ability to engage with their surroundings. The study highlights the importance of nurturing strong parent-child bonds, especially in families with autistic children.